Early discharge as a mediator of greater ICU‐level care requirements in patients not enrolled on the AAML0531 clinical trial: a Children's Oncology Group report. (29th July 2016) - Getz, Kelly D.; Miller, Tamara P.; Seif, Alix E.; Li, Yimei; Huang, Yuan‐Shung; Alonzo, Todd; Gerbing, Robert; Sung, Lillian; Hall, Matthew; Bagatell, Rochelle; Gamis, Alan; Fisher, Brian T.; et al.
Abstract: Previous data suggest that patients enrolled on clinical trials for treatment of cancer have better overall survival than patients who do not enroll; however, short‐term outcomes relative to trial enrollment and corresponding mediators have not been assessed. A cohort of pediatric patients with newly‐diagnosed acute myeloid leukemia was assembled from the Pediatric Health Information System. We evaluated whether patients not enrolled onto Children's Oncology Group trial AAML0531 had greater intensive care unit (ICU)‐level requirements than enrolled patients and whether early discharge after chemotherapy administration mediated this association. Patients not enrolled on AAML0531 were more likely to be discharged early (aOR = 1.40, 95% confidence interval [CI]: 1.02, 1.90) and to require ICU‐level care (aOR = 2.00, 95% CI: 1.06, 3.78) than enrolled patients, but early discharge explained only a small proportion (12.3%) of the absolute difference in ICU‐level care risk. The direct effect of nonenrollment on the need for ICU‐level care was significant (aOR = 1.89, 95% CI: 1.00, 3.94), whereas the indirect effect mediated through early discharge was not (aOR = 1.07, 95% CI: 0.95, 1.19). Factors other than postchemotherapy discharge strategy drive the difference in ICU utilization by trial enrollment status. Abstract : Patients not enrolled on AAML0531 were more likely to be discharged early (aOR = 1.40, 95% confidence interval [CI]: 1.02, 1.90) and to require intensive care unit (ICU)‐level care (aOR = 2.00, 95% CI: 1.06, 3.78) than enrolled patients, but early discharge explained only a small proportion (12.3%) of the absolute difference in ICU‐level care risk. The direct effect of nonenrollment on the need for ICU‐level care was significant (aOR = 1.89, 95% CI: 1.00, 3.94), whereas the indirect effect mediated through early discharge was not (aOR = 1.07, 95% CI: 0.95, 1.19). Factors other than postchemotherapy discharge strategy drive the difference in ICU utilization by trial enrollment status.